2001
DOI: 10.1007/s004280100401
|View full text |Cite
|
Sign up to set email alerts
|

C282Y and H63D mutation of the hemochromatosis gene in German porphyria cutanea tarda patients

Abstract: The high frequency of homo- and heterozygosity for the C282Y and H63D alleles strongly suggests that these mutations are important predisposing factors for PCT in German patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
32
1
3

Year Published

2003
2003
2011
2011

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(41 citation statements)
references
References 22 publications
4
32
1
3
Order By: Relevance
“…(18) encontraron en Norteamérica que el 73% de los pacientes con PCT tenían una o más mutaciones en el gen HFE (23% heterocigotos, 19% homocigotos C282Y; para H63D 23% heterocigotos y 8% homocigotos). Se han publicado hallazgos similares por otros autores (16,(26)(27)(28). En contraste Sampietro y cols.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…(18) encontraron en Norteamérica que el 73% de los pacientes con PCT tenían una o más mutaciones en el gen HFE (23% heterocigotos, 19% homocigotos C282Y; para H63D 23% heterocigotos y 8% homocigotos). Se han publicado hallazgos similares por otros autores (16,(26)(27)(28). En contraste Sampietro y cols.…”
Section: Discussionunclassified
“…La relación entre mutaciones HFE con los índices séricos férricos, la concentración férrica hepática y la fibrosis varía de unos trabajos a otros (2,4,16,18,25,26,28,30,31). En nuestra serie el 80% de los pacientes presentaron elevación de ferritina.…”
Section: Discussionunclassified
“…Additionally, induction of the δ-ALA-synthase increases the amount of δ-aminolevulinic acid, the primary product of the porphyrin synthesis pathway, thus accumulating intermediate products which provoke the symptoms of PCT. The high frequency of homo-and heterozygous allele carriers for the C282Y-and H63D-mutations of HHC among patients with sporadic PCT, as opposed to healthy controls, was demonstrated in several countries, such as Germany [12] , Great-Britain [13] , the Netherlands [14] and Australia [15] . Further studies confirmed the HFE mutations as a risk factor for PCT as well as additional risk factors like alcohol consumption, smoking and hepatitis C virus infection [16][17][18] .…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3] PCT patients usually display hepatic siderosis, and the disease is responsive either to phlebotomy, which presumably acts through iron depletion, or a treatment with low-dose chloroquine or hydroxychloroquine. 1,2 In addition, some PCT patients have quite high levels of hepatic iron associated with the common mutations in the HFE gene (C282Y and H63D), 4,5 which are also found in hereditary hemochromatosis (type I).…”
mentioning
confidence: 99%